Orthodontic treatment-related risks and complications: part II periodontal complications - Tiro, Alisa (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2018)
Introduction: Orthodontic treatment, in addition to patient benefits, includes certain risks and complications that should not beignored. The side-effects of orthodontic therapy all therapists want to avoid or reduce to a minimum.The occurrence of these complications depends on the orthodontic technique, medical knowledge in this field, patient’s generaland oral health, and oral hygiene habits. Part of the risk and complications depend on the patient’s ability to understand andcooperate during the therapy. For this reason, it is a medico-legal obligation to inform our patients about side effects of any medicalintervention what will be undertaken. In the previous issue, an overview of local complications of orthodontic treatment - dentalcomplications was presented. The aim: The aim of this part is to present a detailed overview of the most common complications with local effect- periodontalcomplications in the context of the contemporary attitude of the risks and complications associated with orthodontic treatment. Material and methods: Classification was presented by Graber, 2004th, in its publication, "Risk Management in Orthodontics: AnExpert’s Guide to Malpractice," used as a starting point for the development of this review. A complex search was performed (PubMed, Google Scholar, etc.), with the restriction upon of publication date (beginning with 2004) to find relevant current studies.Search keywords were combinations of words: complication, orthodontic treatment, risks, side effects. Concluding remarks: Periodontal complications are the most common side effects linked with orthodontic treatment according tocontemporary literature. Serious analysis of potential risk for periodontal complications is mandatory for orthodontic patientsbefore the treatment starts. It is the only correct way to minimize complications during and after orthodontic treatment.